The Influence of Board of Directors, Independent Board of Commissioners, Leverage, and Corporate Activities To Disclosure of Sustainability Report. - Eria Nissa Awalia; Ratna Anggraini; Rida Prihatni (Jurnal Ilmiah Wahana Akuntansi, 2015)
This research was intended to examine the influences of board of directors, board of independent commissioner, leverage, and activity of company toward sustainability report disclosure. Sustainability Report Disclosure is the dependent variable sinthis research were measured by GRIG 3.1 Content Index and Checklists. For the independent variables in this research, using board of directors were measured by sum of directors meetings, board of in dependent commissioner were measured by proportion of independent commissioner, leverage were measured by debt to equity, activity of company were measured by total asset turnover. This research uses secondary data which is financial statement. and sustainability report from Indonesian Stock Exchange Listed Companies in 2010-2012. While the sampling method used was purposive sampling method which is overall 39 observations. This research uses multiple regression method to test the hypothesis with SPSS computer program. From the analysis performed in this research, it can be concluded that board of directors, and leverage have no significant influence to sustainability report disclosure. The other hand activity of company has positive influence and significant to sustainability report disclosure. And Board of independent commissioner has negative influence and significant to sustainability reporting disclosure. KeyWords: Board of Directors, Board of Independent Commissioner, Leverage, Activity of Company, and Sustainability Report